A Simulation Study of the Self-Assembly of Coarse-Grained Skin Lipids - Hadley, K. R. (2012)
Computer simulations are an attractive means by which to probe the self-assembly and molecular level organization of lipids in biological membranes. In this work, we study a simple skin lipid system to demonstrate the ability of the coarse-grained models used for fatty acids, cholesterol, and water to self-assemble, thus validating the models for use in further studies of the complex lipid mixtures found in the outermost layer of the skin. Specifically, the ability of the models to predict the correct self-assembled structures from molecular dynamics simulations is compared against those seen experimentally and from all-atom simulations of preassembled bilayers. The nature of the molecular interactions and their roles in the self-assembly process is elucidated and heuristics for self-assembly established. Additionally, the coarse-grained models have been used to characterize the effect of varying cholesterol composition on bilayer properties and the mechanism of bilayer destabilization by short and long chain fatty acids in the presence of cholesterol.